Design and simulation of fused deposition modelling 3D metal printer based on fibre laser technique - Ismail, Siti Iriaty Sa; Mohd Ariffin, Mohd Khairol Anuar; Ismail, Mohd Idris Shah; Hasan, Zaimah; Dezaki, Mohammadreza Lalegani (Akademia Baru Publishing, 2024)
This study aims to design and analysed the structure of the frame of a 30 metal printer. First, this work calculates the static stress on a frame structure. Second, as vibration could affect the effectiveness and performance of a 30 metal printer, this study also concentrates on building a frame structure with minimum vibration. SolidWorks is the software used in this study to sketch and simulate designed 30 models. Finite element analysis (FEA) was used for the simulation part to assess the frame's static and vibration motion analyses. In the analysis using the aluminium 6061 alloy material on the frame design, the result analysed the value at a three-point location. Based on simulation results, the yield strength of the structure is 55.1 x 106 N/m2. The maximum value of von Mises stress does not exceed the yield strength at points 1, 2, and 3. Accordingly, point 2 (365 mm) was selected as the location for the fibre laser head since it had the least amount of vibration. The design is, therefore, capable of withstanding the applied load. In conclusion, a new 30 metal printer's frame design has been analysed to demonstrate its sturdy structure and minimal vibration